(untitled) (International Journal of Engineering and Computer Science, 2015)
Wireless Sensor Networks consists of sensor nodes which move randomly. Energy based routing in wireless sensor network is a demanding assignment. Power Aware Routing which attains application-specified communication delays at low energy cost by adapting transmission power and routing decisions. Some of the major issues in wireless sensor networks are energy consumption, lack of authentication, data integrity and instability of path link between sensor nodes which reduces the popularity of the sensor network. In recent years, the existing methods have focused on attaining either energy consumption or security. Here it consists of optimized multipath routing, power aware energy based routing approach to make the wireless sensor networks more secure with minimum energy consumption. The multipath routing is constructed to achieve high throughput and load balancing. The optimal energy path is established to maintain the data packet flow in the wireless sensor network unobstructed and the energy consumption model is developed to produce the minimum energy consumption.